2016
DOI: 10.1021/acs.chemmater.6b00131
|View full text |Cite
|
Sign up to set email alerts
|

π-Bridge-Independent 2-(Benzo[c][1,2,5]thiadiazol-4-ylmethylene)malononitrile-Substituted Nonfullerene Acceptors for Efficient Bulk Heterojunction Solar Cells

Abstract: Molecular acceptors are promising alternatives to fullerenes (e.g. PC 61 / 71 BM) in the fabrication of high-efficiency bulk-heterojunction (BHJ) solar cells. While solution-processed polymer-fullerene BHJ devices have recently met the 10% efficiency threshold, molecular acceptors have yet to prove comparably efficient with polymer donors. At this point in time, it is important to forge a better understanding of the design parameters that directly impact small-molecule (SM) acceptor performance in BHJ solar ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 67 publications
1
59
0
Order By: Relevance
“…Small molecular acceptors exhibit great advantages of low production costs, easily tunable energy levels, broad absorption range, and potentially better morphological stability in the active blend film . Extensive research efforts have been dedicated in designing novel SMAs that can yield high‐efficiency PSCs . There are generally two classes of SMAs reported with either small (≈1.5 eV) or large (≈2.0 eV) optical bandgaps.…”
Section: Inverted Device Parameters Of the Nonfullerene Pscs The Avementioning
confidence: 99%
“…Small molecular acceptors exhibit great advantages of low production costs, easily tunable energy levels, broad absorption range, and potentially better morphological stability in the active blend film . Extensive research efforts have been dedicated in designing novel SMAs that can yield high‐efficiency PSCs . There are generally two classes of SMAs reported with either small (≈1.5 eV) or large (≈2.0 eV) optical bandgaps.…”
Section: Inverted Device Parameters Of the Nonfullerene Pscs The Avementioning
confidence: 99%
“…AFM images showed that after adding the additives, the blend could form a more uniform film and a clearer phase separation, which was beneficial for the charge transport. Beaujuge and co‐workers designed and synthesized three nonfullerene small molecule acceptors A26, A27, and A28, with BM‐based terminal group. The difference among the three acceptors was the central core varying from fluorine to carbazole and cyclopenta [2, 1‐b: 3, 4‐b′] dithiophene.…”
Section: Nonfullerene Small Molecule Acceptorsmentioning
confidence: 99%
“…The solution and thin-film UV-vis spectra shown in Figure 2a indicate that swapping alkyls (SM1) for acrylate substituents (SM2) in [2F]Q redshift the spectral absorption by up to ≈120 nm, corresponding to a notable reduction in optical gap of 0.3 eV. Following the same trend in IP values, experimental estimates were determined via photoelectron spectroscopy in air (PESA): 5.20 eV for SM2 and 5.11 eV for SM1 (here, we note that PESA-estimated values are in general lower than DFT-calculated ones, [18,27,28] but the trends remain meaningful). [26] Examinations of the main-chain conformation and π-electron delocalization patterns by density functional theory (DFT; modeling with the gap-tuned, longrange-corrected (LRC) hybrid functional ωB97XD/6-31G(d,p), cf.…”
Section: Design Synthesis and Materials Propertiesmentioning
confidence: 89%